2012
DOI: 10.1210/en.2012-1030
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Prostate Cancer Is Prevented in ERαKO Mice and Stimulated in ERβKO TRAMP Mice

Abstract: Previous evidence suggests soy genistein may be protective against prostate cancer, but whether this protection involves an estrogen receptor (ER)-dependent mechanism is unknown. To test the hypothesis that phytoestrogens may act through ERα or ERβ to play a protective role against prostate cancer, we bred transgenic mice lacking functional ERα or ERβ with transgenic adenocarcinoma of mouse prostate (TRAMP) mice. Dietary genistein reduced the incidence of cancer in ER wild-type (WT)/transgenic adenocarcinoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 74 publications
3
60
0
2
Order By: Relevance
“…A similar remarkable effect of ERb agonists has been observed in the TRAMP mouse (transgenic mouse model for prostate cancer; Gingrich et al 1996). In this mouse model of prostate cancer, dietary genistein, is an ERbdependent pathway, reduced the incidence of prostate cancer and the severity of the invasive cancer was increased in ERb K/K mice (Slusarz et al 2012). One other confounding factor occurring in prostate cancer is the expression of the ERb splice variant ERb2.…”
Section: Studies On Erbmentioning
confidence: 89%
“…A similar remarkable effect of ERb agonists has been observed in the TRAMP mouse (transgenic mouse model for prostate cancer; Gingrich et al 1996). In this mouse model of prostate cancer, dietary genistein, is an ERbdependent pathway, reduced the incidence of prostate cancer and the severity of the invasive cancer was increased in ERb K/K mice (Slusarz et al 2012). One other confounding factor occurring in prostate cancer is the expression of the ERb splice variant ERb2.…”
Section: Studies On Erbmentioning
confidence: 89%
“…Mice with PCa lacking ERα or ERβ treated with phytoestrogens showed that cancer did not progress in ERαKO mice whereas ERβΚΟ mice presented an increasing incidence of poorly differentiated carcinoma (Gleason scores 4 and 5) (78). Re-expression of ERβ via phytoestrogens elicited antiandrogenic effects, including downregulation of AR and its coactivators (79).…”
Section: Phytoestrogensmentioning
confidence: 99%
“…20,23 The function of p53 and Rb is abrogated by SV-40 large T antigen; as a result, TRAMP male mice develop spontaneous progressive stages of PCa with time from early lesions of prostatic intraepithelial neoplasia (PIN) to late stage adenocarcinoma. 20,23 Furthermore, this PCa model has been also crossed with other genetically manipulated mice so as to generate bigenic mice, [28][29][30][31] which are employed to study the role of specific molecules in PCa progression. The changing patterns of CDKs and cyclins have been also well characterized during the progression of PCa in TRAMP model; 32 notably, we have reported the increased expression of p21 protein in TRAMP prostate with advanced stage of the disease.…”
Section: Introductionmentioning
confidence: 99%